2005
DOI: 10.1016/j.scitotenv.2004.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Slow release chelate enhancement of lead phytoextraction by corn (Zea mays L.) from contaminated soil—a preliminary study

Abstract: (2005). Slow release chelate enhancement of lead phytoextraction by corn (Zea mays L.) from contaminated soil: A preliminary study. Science of The Total Environment, 339(1-3), 179-187. DOI: 10.1016179-187. DOI: 10. /j.scitotenv.2004 Published in: Science of The Total Environment Queen's University Belfast -Research Portal: Link to publication record in Queen's University Belfast Research Portal General rights Copyright for the publications made accessible via the Queen's University Belfast Research Portal is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 22 publications
5
30
0
Order By: Relevance
“…Heavy metal contamination of soils is an important environmental issue because of its impact on soil preservation and human health (Li et al, 2005). In São Paulo State, Brazil, 4,131 contaminated sites have been identified, and 543 of them are contaminated with a variety of metals (CETESB, 2011).…”
Section: Phytoremediationmentioning
confidence: 99%
“…Heavy metal contamination of soils is an important environmental issue because of its impact on soil preservation and human health (Li et al, 2005). In São Paulo State, Brazil, 4,131 contaminated sites have been identified, and 543 of them are contaminated with a variety of metals (CETESB, 2011).…”
Section: Phytoremediationmentioning
confidence: 99%
“…To lower the speed of release of Pb by EDTA, Shen et al (2002) tested split applications of EDTA and found that Pb was leached much more slowly with split application than single application. Li et al (2005) developed a controlled-release EDTA by coating the EDTA with a layer of silicate. Unfortunately, the silicate-coated EDTA was released within a short period, probably due to the properties of the coating materials.…”
Section: Z Xie Et Almentioning
confidence: 99%
“…Therefore, even if suitable irrigation strategies are implemented as proposed (Blaylock et al, 1997;Madrid et al, 2003), the potential of metals leaching in synthetic chelator-treated soil is still high during seasons of intense rainfall. In a preliminary study that used 1 week-old seedlings, Li et al (2005) registered that turning EDTA into a slow-release compound through coating of the EDTA granules with silicates could reduce the risk of metal leaching. More studies with older plants on a field scale are needed to assess the usefulness of this technique for overcoming the leaching risks while maintaining a high metal uptake rate by plants.…”
Section: The Use Of Chemical Amendments To Enhance Metal Phytoextractmentioning
confidence: 99%
“…For instance, coating natural organic acids to maintain a stead concentration of metal-organic acids complexes in soil solution, as done to EDTA by Li et al (2005), could be an alternative. Apparently fast biodegradation rather than the low organic acid ability to solubilize metals is the main reason for unsuccessful phytoextraction (Krishnamurti et al, 1997;Nascimento et al, 2006).…”
Section: The Use Of Chemical Amendments To Enhance Metal Phytoextractmentioning
confidence: 99%